Managed alcohol programs in the context of Housing First. Issue 4 (5th December 2019) - Schiff, Rebecca; Pauly, Bernie; Hall, Shana; Vallance, Kate; Ivsins, Andrew; Brown, Meaghan; Gray, Erin; Krysowaty, Bonnie; Evans, Joshua
Abstract : Purpose: Recently, Managed Alcohol Programs (MAPs have emerged as an alcohol harm reduction model for those living with severe alcohol use disorder (AUD) and experiencing homelessness. There is still a lack of clarity about the role of these programs in relation to Housing First (HF) discourse. The authors examine the role of MAPs within a policy environment that has become dominated by a focus on HF approaches to addressing homelessness. This examination includes a focus on Canadian policy contexts where MAPs originated and are still predominately located. The purpose of this paper is to trace the development of MAPs as a novel response to homelessness among people experiencing severe AUD and to describe the place of MAPs within a HF context. Design/methodology/approach: This conceptual paper outlines the development of discourses related to persons experiencing severe AUD and homelessness, with a focus on HF and MAPs as responses to these challenges. The authors compare the key characteristics of MAPs with "core principles" and values as outlined in various definitions of HF. Findings: MAPs incorporate many of the core values or principles of HF as outlined in some definitions, although not all. MAPs (and other housing/treatment models) provide critical housing and support services for populations who might not fit well with or who might not prefer HF models. Originality/value: The "silver bullet" discourse surrounding HF (and harm reduction) can obscure the importance of programs (such as MAPs) that do not fully align with all HF principles and program models. This is despite the fact that MAPs (and other models) provide critical housing and support services for populations who might fall between the cracks of HF models. There is the potential for MAPs to help fill a gap in the application of harm reduction in HF programs. The authors also suggest a need to move beyond HF discourse, to embrace complexity and move toward examining what mixture of different housing and harm reduction supports are needed to provide a complete or comprehensive array of services and supports for people who use substances and are experiencing homelessness.